Inhibition of retinol oxidation by ethanol in the rat liver and colon. Issue 6 (1st December 2000) - Parlesak, A; Menzl, I; Feuchter, A; Bode, J C; Bode, C
Abstract : BACKGROUND: Epidemiological evidence has been presented for an increased risk of development of colon cancer after chronic alcohol abuse. Alcohol is degraded by cytosolic alcohol dehydrogenases that also are capable of retinol oxidation. Inhibition of retinol oxidation to retinoic acid has been shown to occur in parallel with profound impairment of intracellular retinoid signal transduction and loss of cell differentiation control. AIMS: In the present study, the change in cytosolic retinol oxidation and retinoic acid formation by ethanol concentrations that occur in body tissues in humans after social drinking was measured in cells from the liver, and small and large intestine of the rat. RESULTS: The specific catalytic efficiency Vmax /Km (ml/min/g) of cytosolic retinol oxidation in the large intestine (28.9) was found to be distinctly higher than that in the liver (3.4), while the efficiency in the small intestine was negligible (0.20). In the presence of increasing ethanol concentrations (9, 17, and 34 mM), Vmax /Km for retinol oxidation decreased in a dose dependent manner to 7.8% of the initial value in the large intestine and to 12% in the liver. The Vmax /Km of retinoic acid formation in the liver cytosol decreased to 15%. CONCLUSIONS: Our data demonstrate impairment of hepatic and intestinal cytosolic retinol oxidation and retinoic acid formation by ethanol at concentrations in body tissues after social drinking in humans. The results suggest that the increased risk of developing colorectal neoplasias after alcohol abuse may, at least in part, be caused by impaired retinoid signal transduction.